2020
DOI: 10.1186/s13071-020-04372-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and genotyping of Anaplasma marginale and co-infection with piroplasms and other Anaplasmataceae in cattle and buffaloes from Egypt

Abstract: Background Anaplasma marginale is an obligate intracellular bacterium and the main cause of bovine anaplasmosis in tropical and subtropical regions. In Egypt, data regarding the prevalence of A. marginale in ruminant hosts and of the circulating genotypes is lacking. This study therefore aimed to (i) investigate the presence, epidemiology and genotypes of A. marginale in cattle and buffaloes in Egypt, (ii) to evaluate suitable diagnostic tools and (iii) to identify co-infections of A. marginale… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 44 publications
2
35
0
1
Order By: Relevance
“…Among the169 cattle, 4/14; 14/129; 4/26 were infected by A. marginale in exotic pure breeds, Crossbreed and Atlas Brown breed, respectively. All cattle breeds were infected by A. marginale, similarly AL-Hosary et al (2020) and Ait Hamou et al (2012) showed that A. marginale prevalence did not vary according to cattle breed.…”
Section: Symptomsmentioning
confidence: 60%
See 2 more Smart Citations
“…Among the169 cattle, 4/14; 14/129; 4/26 were infected by A. marginale in exotic pure breeds, Crossbreed and Atlas Brown breed, respectively. All cattle breeds were infected by A. marginale, similarly AL-Hosary et al (2020) and Ait Hamou et al (2012) showed that A. marginale prevalence did not vary according to cattle breed.…”
Section: Symptomsmentioning
confidence: 60%
“…All cattle breeds were infected by A. marginale , similarly AL‐Hosary et al. (2020) and Ait Hamou et al. (2012) showed that A. marginale prevalence did not vary according to cattle breed.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Co-infection with Babesia and Anaplasma is a common finding in cattle: A. marginale and B. bigemina , and Anaplasma sp. and B. bigemina have been simultaneously detected in the same individuals in Egypt and Ethiopia, respectively [ 45 , 46 ]. The effect of mixed infections on clinical outcomes needs to be evaluated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Anaplasma marginale causes bovine anaplasmosis resulting in economic losses to the cattle industry due to a significant reduction of beef and dairy production (7). More recently, some coinfections with piroplasmas and other Anaplasmataceae reported in cattle and buffaloes show the circulation of diverse genotypes of A. marginale worldwide (8).…”
Section: A Brief Overview Of Tick-borne Diseases In Cattlementioning
confidence: 99%